2024
DOI: 10.3390/ani14060906
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Near-Infrared Multiwavelength Locked System Laser Therapy on Skin Microbiome in Atopic Dogs

Sara Muñoz Declara,
Aldo D’Alessandro,
Agnese Gori
et al.

Abstract: Photobiomodulation (PBM) is a newly adopted consensus term to replace the therapeutic application of low-level laser therapy. It has been suggested that PMB influences the microbiome which, in turn, has increasingly been shown to be linked with health and disease. Even though the use of PBM has also grown dramatically in veterinary medicine, there is still a lack of evidence supporting its effect in vivo. Our objective was to investigate the impact of a dual-wavelength near-infrared laser source (Multiwaveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…It is also generally understood that specific wavelengths affect bacteria in different ways, with UV and blue wavelengths generally considered to be more destructive than red or infrared light [73,[81][82][83][84]. Interestingly, the studies we reviewed suggest that overall, UV light therapy results in an increase in microbial diversity and a decrease in pathogenic bacteria such as S. aureus, whereas laser therapy, regardless of wavelength, leads to decreased bacterial densities in all species tested [40][41][42][43][44]49,[51][52][53][54]58,59,61]. The reasons for this are unclear, but may be due to the optical amplification innate in laser therapy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is also generally understood that specific wavelengths affect bacteria in different ways, with UV and blue wavelengths generally considered to be more destructive than red or infrared light [73,[81][82][83][84]. Interestingly, the studies we reviewed suggest that overall, UV light therapy results in an increase in microbial diversity and a decrease in pathogenic bacteria such as S. aureus, whereas laser therapy, regardless of wavelength, leads to decreased bacterial densities in all species tested [40][41][42][43][44]49,[51][52][53][54]58,59,61]. The reasons for this are unclear, but may be due to the optical amplification innate in laser therapy.…”
Section: Discussionmentioning
confidence: 98%
“…It is generally associated with an increase in microbiome diversity [40][41][42][43][44][45][46][47]. However, some studies found no significant change in this regard [48,49].…”
Section: Phototherapy Significantly Alters the Skin Microbiomementioning
confidence: 99%
See 1 more Smart Citation